2000
DOI: 10.1002/1096-9918(200008)29:8<544::aid-sia901>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy characterization of ultrafiltration membranes: correspondence between surface pore dimensions and molecular weight cut-off

Abstract: Atomic force microscopy (AFM) has been used to quantify the mean surface pore diameters of a family of five ultrafiltration membranes with molecular weight cut-off (MWCO) in the range 1000-10 000. High aspect ratio tips were used and the images were treated with fast Fourier transform filtering to remove distortions. The mean pore diameters were found to be in the range 1.93-3.14 nm, increasing systematically with the MWCO. Mean pore diameters have also been evaluated from the MWCO values using three published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Table 1 gives the MWs and suppliers for the commercial PEG and purer PEG standard used in the method. The properties of commercial membranes used as well as the filtration pressures are provided in 6 GE Osmonics™ GE 1000 [34,35] Composite Polyamide NF…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 gives the MWs and suppliers for the commercial PEG and purer PEG standard used in the method. The properties of commercial membranes used as well as the filtration pressures are provided in 6 GE Osmonics™ GE 1000 [34,35] Composite Polyamide NF…”
Section: Methodsmentioning
confidence: 99%
“…1.88±0.088 1.08±0.061 1.12 1294±20 1000 [34,35] GE Osmonics™ GH 3.22±0.17 1.71±0.060 3.33 1866±373 1000-2500 [30,34,36,37] GE Osmonics™ GK 9.28±0.99 5.64±0.53 5.66 3956±716 2000-3500 [30,34,36,38] TriSep UA60 9.35±0.73 5.07±0.38 7.94 <678 1000-3500 [39] Millipore Ultracel PLAC04310 2.45±0.062 1.98±0.019 ---1030±62 1000 [40] Millipore Ultracel PLBC04310 6.98±0.70 4.64±0.35 ---1404±31 1000-3000* [41,42] * Manufacturer states a MWCO of 3000 but notes that the MWCO could be 2-3 times smaller than the molecular weight of the solute to be retained when using regenerated cellulose. ) indicates that it may be that the MWCO of the supplied membranes is in fact incorrect.…”
Section: Ge Osmonics™ Gementioning
confidence: 99%
“…The results indicated that the average pore diameter of the five membranes fell within the range of 1.93–3.14 nm, increasing with the rise in MWCO. They also used MWCO to estimate the aperture, and the results showed good consistency, which also confirmed the role of AFM in the study of MWCO …”
Section: Application Of Afm In the Research Of Membrane Separationmentioning
confidence: 55%
“…They also used MWCO to estimate the aperture, and the results showed good consistency, which also confirmed the role of AFM in the study of MWCO. 302 The primary limitation affecting the resolution of AFM measurements is the size of the tip. When the scan tip's size is comparable to the membrane pore's aperture, it becomes impractical for the tip to enter the pore and accurately determine its exact size.…”
Section: Acs Esandt Engineeringmentioning
confidence: 99%